ESTIMATION OF INBREEDING COEFFICIENT IN REGISTERED BROWN SWISS BULLS OF PERU, YEAR 2003 - Oré C., Juan (2009)
Inbreeding can cause a depression in fertility performance, health and productivity of dairy cows and other animal husbandry species. The aim of this study was to estimate the inbreeding coefficient of Brown Swiss bulls registered in year 2003 and establish the origin of their sires and dam’s sires. Records of 4 generations of 113 pedigree bulls registered in the Peruvian Brown Swiss Association in 2003 were analyzed, processing a total of 3616 pedigree certificates. The computer program Pedigree Viewer 5.5 was used to determine the inbreeding coefficient of these bulls. The average inbreeding coefficient was 3.6%, and 68.2% of the analyzed population had an inbreeding coefficient of less than 4%. Besides, it was observed that 41.2% of the sire’s sires evaluated had Peruvian origin and 41% of the dam’s sires (maternal grandfather) had Peruvian origin too. The inbreeding coefficient obtained was relatively low, though, it is advisable that animal breeding programmes analyze the genealogical tree of the dam and sire in order to control inbreeding in herds.